Deciphering the LRRK code: LRRK1 and LRRK2 phosphorylate distinct Rab proteins and are regulated by diverse mechanisms. Issue 3 (12th February 2021) - Malik, Asad U.; Karapetsas, Athanasios; Nirujogi, Raja S.; Mathea, Sebastian; Chatterjee, Deep; Pal, Prosenjit; Lis, Pawel; Taylor, Matthew; Purlyte, Elena; Gourlay, Robert; Dorward, Mark; Weidlich, Simone; et al.
Abstract : Autosomal dominant mutations in LRRK2 that enhance kinase activity cause Parkinson's disease. LRRK2 phosphorylates a subset of Rab GTPases including Rab8A and Rab10 within its effector binding motif. Here, we explore whether LRRK1, a less studied homolog of LRRK2 that regulates growth factor receptor trafficking and osteoclast biology might also phosphorylate Rab proteins. Using mass spectrometry, we found that in LRRK1 knock-out cells, phosphorylation of Rab7A at Ser72 was most impacted. This residue lies at the equivalent site targeted by LRRK2 on Rab8A and Rab10. Accordingly, recombinant LRRK1 efficiently phosphorylated Rab7A at Ser72, but not Rab8A or Rab10. Employing a novel phospho-specific antibody, we found that phorbol ester stimulation of mouse embryonic fibroblasts markedly enhanced phosphorylation of Rab7A at Ser72 via LRRK1. We identify two LRRK1 mutations (K746G and I1412T), equivalent to the LRRK2 R1441G and I2020T Parkinson's mutations, that enhance LRRK1 mediated phosphorylation of Rab7A. We demonstrate that two regulators of LRRK2 namely Rab29 and VPS35[D620N], do not influence LRRK1. Widely used LRRK2 inhibitors do not inhibit LRRK1, but we identify a promiscuous inhibitor termed GZD-824 that inhibits both LRRK1 and LRRK2. The PPM1H Rab phosphatase when overexpressed dephosphorylates Rab7A. Finally, the interaction of Rab7A with its effector RILP is not affected by LRRK1 phosphorylation and we observe that maximal stimulation of the TBK1 or PINK1 pathway does not elevate Rab7A phosphorylation. Altogether, these findings reinforce the idea that the LRRK enzymes have evolved as major regulators of Rab biology with distinct substrate specificity.